Fire Detection in H.264 Compressed Video - Savci, Murat Muhammet; Yildirim, Yasin; Saygili, Gorkem; Toreyin, Behcet Ugur (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2019)
In this paper, we propose a compressed domain fire detection algorithm using macroblock types and Markov Model in H.264 video. Compressed domain method does not require decoding to pixel domain, instead a syntax parser extracts syntax elements which are only available in compressed domain. Our method extracts only macroblock type and corresponding macroblock address information. Markov model with fire and non-fire models are evaluated using offline-trained data. Our experiments show that the algorithm is able to detect and identify fire event in compressed domain successfully, despite a small chunk of data is used in the process.